Review and comparison of finite element flexural–torsional models for non-linear behaviour of thin-walled beams. (February 2015) - Mohri, Foudil; Damil, Noureddine; Potier-Ferry, Michel
Abstract: The authors have developed a beam finite element model in large torsion context for thin-walled beams with arbitrary cross sections[1] . In the model, the trigonometric functions of the twist angle θ x ( c  = cos θ x  − 1 and s  = sin θ x ) were included as additional variables in the whole model without any assumption. In the present paper, three other 3D finite element beams are derived according to three approximations based on truncated Taylor expansions of the functions c and s (cubic, quadratic and linear). A finite element approach of these approximations is carried out. Finally, it is worth mentioning that the promising results obtained in[1, 2] encourage the authors to extend the formulation of the model in order to include load eccentricity effects. Solution of the non-linear equations is made possible by Asymptotic Numerical Method (ANM)[3] . This method is used as an alternative to the classical incremental iterative methods. Many comparison examples are considered. They concern the non-linear behaviour of beams under twist moment and the post buckling behaviour of struts under axial loads or the beam lateral buckling under eccentric bending loads. The obtained results highlight the discrepancies between the various approximations often employed in thin-walled beams literature for the geometrically non-linear analysis of beams in flexural–torsional behaviour.